Pentingnya Peranan Orang Tua dan Guru dalam Meningkatkan Akhlak Anak - Baharudin, Adi; Maryono, Dicky (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
In this modern era, morals are very crucial in life, especially in children. Parents as the first home for children have a very important role in fostering children in forming good morals. Teachers are also very influential in providing moral education for children so that they are good. This considers the points to see the role of parents and teachers in children's morals. This kind of search is qualitative through library searches, the source of information comes from writing in the form of books, copyrighted works, and other copyrighted sources found in print and electronic media, which are related to the role of parents and teachers in children's morals. The information checking strategy used can be in the form of a qualitative descriptive analysis strategy. The results of this study indicate that parents and teachers have a big contribution in structuring children's morals. This underlines that in a family parents and teachers are role models for children.